Effects of the Moreton waves on the structure of Coronal Mass Ejections Events (CMEs) based on solar radio burst type II (SRBT II) characteristics / Nur Hidayah Zainol - Zainol, Nur Hidayah (2019)
The Moreton wave (also known as flare wave) has been extensively studied in the hope of explaining the relation between solar flare, Coronal Mass Ejections (CMEs) and Solar Radio Burst Type II (SRBT II) phenomena. It is interpreted as an intersection of coronal Magneto-hydrodynamic (MHD) fast mode shock wave and solar chromosphere. It is well known that the occurrence of CME is always associated with both solar flare and SRBT II. Furthermore, SRBT II is also originated from the MHD fast mode shock wave theory. Previous research showed that Moreton wave constantly associated with solar flare event.